2005
DOI: 10.1021/tx049662i
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Speciation of Uranium in Water Does Not Influence Its Absorption from the Gastrointestinal Tract of Rats

Abstract: Studies of the chemical speciation of uranium in water can enhance the knowledge of the mechanisms of its absorption from the gastrointestinal tract and its storage in the body. They can also help to improve the dosimetric models recommended by the International Commission on Radiological Protection (ICRP). The aim of this work was to assess the influence of uranium speciation on its absorption from the gastrointestinal tract by using both computer speciation modeling and direct measurement of the fractional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The discrepancy is very likely due to the difference of the administration mode. Indeed, previous study demonstrated that only 0.5% of uranium present in drinking water was absorbed into blood by the gastrointestinal system [57]. …”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy is very likely due to the difference of the administration mode. Indeed, previous study demonstrated that only 0.5% of uranium present in drinking water was absorbed into blood by the gastrointestinal system [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have been published regarding the theoretical and analytical speciation of actinides or lanthanides in simulated biological fluids such as plasma, saliva, gastric fluid, urine and pancreatic fluids, in order to predict their behavior in the human body. [33][34][35][36][37][38][39] The metals' speciation and solubility were shown to be dependent on the pH, their concentration, the fluid composition and the ionic strength of each system. It must be noted that the theoretical speciation of metals in culture media used in toxicological studies is rarely addressed, although it is a very useful prediction tool for investigators.…”
Section: Speciation In Extracellular Mediummentioning
confidence: 99%
“…Nevertheless, this study remains speculative from a public health point of view. Modeling of uranium speciation in drinking water with high uranium content and its consequences in the event of ingestion has already been performed in rats (19), but with synthetic mixtures of uranium without potentially speciation-modifying agents such as calcium (Ca 2+ ), and without real environmental sampling. On the other hand, the J-Chess modeling program for speciation has been used for predicting uranium (VI) speciation in different simulated human biological fluids (saliva, gastric juice, plasma) (20).…”
Section: Introductionmentioning
confidence: 99%